2020
DOI: 10.1007/s13178-020-00484-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal Values, Gender Stereotypes, and School Climate on Homophobic Bullying: a Multilevel Analysis

Abstract: Introduction Schools are among the most homophobic social contexts, where students who do not conform to gender norms are at high risk of stigma and discrimination. Method Using a multilevel approach, the aim of the current was to examine whether adolescents' engagement in homophobic bullying behavior was associated with personal values and stereotyped victim-blaming attributions at individual level, and perceptions of school as a community and frequency of teachers' reaction to bullying incidents at classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…To help the reader these two items have been translated into English). Then, the findings confirm links between stigma and deviant attitudes, which can give rise to discrimination and violence, as suggested by many authors [32,45,46].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…To help the reader these two items have been translated into English). Then, the findings confirm links between stigma and deviant attitudes, which can give rise to discrimination and violence, as suggested by many authors [32,45,46].…”
Section: Resultssupporting
confidence: 84%
“…This effect is amplified for students who break the stereotypes "the violation of racial and ethnic stereotypes may created bullying victimization among racial and ethnic minority youth" ( [31], p. 559). Secondly, stereotyped gender attributions are predictors of bullying behaviors, especially in the form of homophobic bullying [32]. As mentioned above, the relationship between children and parents is a strong predictor of both bullying and victimisation behaviours.…”
Section: Introduction and Objectivesmentioning
confidence: 98%
“…Benish-Weisman et al ( 2017 ) found that aggressive behavior was positively related to self-enhancement while negatively related to self-transcendence across different cultures (e.g., Germany, Italy, Israel, and the United States). This relationship was also found in homophobic bullying (Bacchini et al, 2020 ), interpersonal violence (Rossi et al, 2019 ), and lawbreaking behavior (Borg & Hermann, 2020 ). Aggressive behavior was found to have weak relationships with openness to change and conservation values, varying across studies and contexts (Benish-Weisman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 79%
“…Specific values have been associated with increased or decreased stigmatization and prejudice toward certain outgroup members. For example, individuals who endorse conservation values tend to have more prejudice toward immigrants (Davidov et al, 2008;Falanga et al, 2015) and individuals from sexual minorities (Bacchini et al, 2021;Donaldson et al, 2017;Kuntz et al, 2015). They are less likely to engage with members of low-status groups (Sagiv & Schwartz, 1995) and have negative affective responses and judgment toward members of stigmatized groups (i.e., drug users; Skinner et al, 2007).…”
Section: Mechanisms and Conditions Of Cnm Stigmatizationmentioning
confidence: 99%